FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN MUSCULOSKELETAL DISORDERS PADA PORTER DI STASIUN GAMBIR TAHUN 2023 - Farhah Sukma Dewi (2023)
Porter is a job that has a risk of musculoskeletal disorders due to lifting weights and placing emphasis on one particular body part. In addition, Porters at Gambir Station have long working hours which can cause fatigue and further increase the risk of musculoskeletal disorders. These complaints can be caused by various factors, including individual factors and occupational factors. The purpose of this study was to identify the factors associated with musculoskeletal disorders at Porter's Gambir Station in 2023. The research design used in this study was cross-sectional. This study involved 120 people with a purposive sampling method. The results of the analysis stated that there was a significant relationship between age (p-value = 0.007) and work posture (p-value = 0.000) with complaints of musculoskeletal disorders. The work posture variable is the most dominant factor affecting complaints of musculoskeletal disorders, with a POR=15.6 (95% CI: 4.134-58.885). Therefore, it is necessary to improve posture when working by the workers and the company following the existing risk control hierarchy. Keywords: Musculoskeletal Disorders, Individual Factors, Occupational Factors, Porter